Mutagenesis, screening and isolation of Brettanomyces bruxellensis mutants with reduced 4‑ethylphenol production - Álvarez Gaona, Izmari Jasel (2021)
Fil: Álvarez Gaona, Izmari Jasel. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Agropecuaria Mendoza; Argentina